2008
DOI: 10.1371/journal.pgen.1000018
|View full text |Cite|
|
Sign up to set email alerts
|

Functional Characterization of Variations on Regulatory Motifs

Abstract: Transcription factors (TFs) regulate gene expression through specific interactions with short promoter elements. The same regulatory protein may recognize a variety of related sequences. Moreover, once they are detected it is hard to predict whether highly similar sequence motifs will be recognized by the same TF and regulate similar gene expression patterns, or serve as binding sites for distinct regulatory factors. We developed computational measures to assess the functional implications of variations on reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 34 publications
2
16
0
Order By: Relevance
“…In a recent study, this has been shown to be the case for ComK binding sites in B. subtilis, in which transcription activation was almost completely abolished when the second thymine of the K-box was mutated into a guanine, even though the rest of the motif stayed intact (287). Similar results were also reported by Michal et al for the Ndt80 motif in the eukaryote S. cerevisiae (209) and by Francke et al for the LacI family, where the central CG nucleotides in the motif are essential for TF binding (89).…”
Section: Interdependency Of Tfbs Nucleotidessupporting
confidence: 80%
“…In a recent study, this has been shown to be the case for ComK binding sites in B. subtilis, in which transcription activation was almost completely abolished when the second thymine of the K-box was mutated into a guanine, even though the rest of the motif stayed intact (287). Similar results were also reported by Michal et al for the Ndt80 motif in the eukaryote S. cerevisiae (209) and by Francke et al for the LacI family, where the central CG nucleotides in the motif are essential for TF binding (89).…”
Section: Interdependency Of Tfbs Nucleotidessupporting
confidence: 80%
“…Further elucidation of the binding mechanisms of TFs to DNA is crucial for reducing false-positives. For example, Michal and co-workers studied the effect of cis-element variation on the pattern of target gene expression (28). Relationships between TFBSs and flanking sequences also require further study (29).…”
Section: Discussionmentioning
confidence: 99%
“…Yet, previous studies have shown that even low-affinity TF-DNA interactions can play an important role in eukaryotic transcriptional regulation (Tanay, 2006;Segal et al, 2008). Although several computational methods have been proposed for genome-wide detection of functional single nucleotide variants in TFBSs (Andersen et al, 2008;Michal et al, 2008;Torkamani and Schork, 2008), to the best of our knowledge, the synergistic effects of the nucleotide variants in TFBSs and their coTFs have not been considered in a genome-wide scale. These factors motivated us to conduct a more comprehensive analysis to infer the relationships between variable positions in TFBSs and their co-TFs.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have posited that nucleotide substitutions at invariable positions usually result in binding site loss, while different nucleotides at variable positions could be functionally equivalent (Mirny and Gelfand, 2002;Moses et al, 2003). However, a significant number of studies have shown that nucleotide variants at variable positions in a TFBS can still cause differences in gene expression (Segal et al, 2007;Andersen et al, 2008;Michal et al, 2008;Swamy et al, 2009).…”
Section: Introductionmentioning
confidence: 99%